INCREASING VOCABULARY THROUGH HANGMAN GAME BY STUDENTS’ OF SMPN 3 MAKASSAR - Asmarani Harma; A Mulyani Kone; Lusy Anggraeni (Universitas Muhammadiyah Semarang, 2021)
The writer of this study wants to know how the 9.2 grade students at SMPN 3 Makassar are progressing in their vocabulary learning. This was a classroom action research (CAR). The participants in this study were 30 SMPN 3 Makassar 9.2 grade students. In order to represent the population as a study, 22 students out of 30 were chosen. This study was performed in one cycle with Hangman Game as the media for learning vocabulary. The author concluded that in the first cycle, students' involvement in the learning process improved, as did their comprehension of vocabulary. and have had success using the Hangman Game to expand their vocabulary. Aside from that, Hangman Game was a good media for students in SMPN 3 Makassar to learn vocabulary because they needed to refresh their minds after thinking seriously and hardly all day. The majority of students improved their vocabulary as a result of this result.